Ethnic enclaves on the territory of Central Asian states: sustainability factors and their conflictogenic potential - Dosmurzinov Р.К.; Pussyrmanov Н.С. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
The article presents the results of the study of ethnic enclaves on the territory of the countries of the Central Asian region. The aim of the study was to identify the factors of stability of ethnic enclaves and their potential for conflict. The main method was the historical method; the study broadly reveals the background of ethnic enclaves. The main factor of sustainability of ethnic enclaves was determined to be the fact that enclaves are rural settlements where the population is mainly engaged in agriculture. On the basis of the conflictogenicity scale developed by the author of the study, the situation in ethnic enclaves were observed. The study revealed that the media play a major role in the development of the situation in ethnic enclaves. Thus, ethnic enclaves in Central Asia constitute a complex socio-territorial phenomenon shaped by historical, political, and economic factors. Their stability is largely ensured by the rural pattern of settlement, a high level of social cohesion, and the population’s orientation toward traditional forms of economic activity. At the same time, resource scarcity, the incompleteness of border delimitation processes, and the politicization of ethnicity increase the conflict potential of certain enclaves. Mass media and modern communication channels play a significant role in either escalating or containing tensions. Overall, effective regulation of the situation surrounding ethnic enclaves requires a comprehensive interstate approach that takes into account both the historical specificity of the region and contemporary socio-political realities.